2013
DOI: 10.2478/s11536-012-0125-6
|View full text |Cite
|
Sign up to set email alerts
|

Four years of EZ-IO® system in the preand in-hospital emergency setting

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…28,38 Additionally, 15 studies provided data on insertion success by IO device. 24-27,30,31,33,36,37,43,44,50,52,54,55 The EZ-IO device was most used and most successful amongst these studies. The findings are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…28,38 Additionally, 15 studies provided data on insertion success by IO device. 24-27,30,31,33,36,37,43,44,50,52,54,55 The EZ-IO device was most used and most successful amongst these studies. The findings are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 98%
“…Overall, the majority of articles used an EZ-IO batterypowered driver with high success rates, upwards of 90%, and a sub-analysis with trauma exclusive papers did not reveal changes in this high EZ-IO success rates. 8,[24][25][26][27][28][29][30][33][34][35]37,43,50,54 Only 1 retrospective review reported an EZ-IO overall success rate of 81%, but when compared to the Jamshidi with a 68% success rate, was still significantly higher. 52 Other common IO devices included the B.I.G and NIO and comparatively had varying rates of overall success, ranging from 50 to 59% and 68%, respectively.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations